The development of the nursing profession in a globalised context: a qualitative case study in Kerala, India - Timmons, Stephen; Evans, Catrin; Nair, Sreelekha (Elsevier, 2016)
In the paper, we are looking at the relationship between globalisation and the professional project, using nursing in Kerala as an exemplar. Our focus is on the intersection of the professional project, gender and globalisation processes. Included in our analysis are the ways in which gender affects the professional project in the global south, and the development of a professional project which it is closely tied to global markets and global migration, revealing the political-economic, historical, and cultural factors that influence the shape and consequences of nurse migration.